Childhood traumas and dissociative experiences among individuals with substance use disorders in Eastern Turkey. - Aktas, Mehmet Cihad; Ayhan, Cemile Hurrem; aktaş, Sakine; Bayram, Zilan (Journal of Substance Use, 2025)
Objective: The aim of this study was to determine the relationship between childhood trauma and dissociative experiences and t socio demographic factors affecting them among individuals with substance use disorders living in Eastern Turkey using a descriptive cross-sectional design. Methods: This study conducted with 173 individuals with substance use disorders treated at the SBU Van Training and Research Hospital Alcohol and Substance Addiction Treatment Centre (ASATC) in Eastern Turkey between April 2023 and June 2023. The research data were collected using the "Sociodemographic Information Form", "Dissociative Experiences Scale" and "Childhood Trauma Questionnaire". Results: The mean score of the childhood trauma questionnaire was 34.89 ± 14.19. The mean score of the dissociative experiences scale of participants was 11.63 ± 11.75. It was found that the mean score of sexual abuse subscale of the participants differed according to age, education status and family substance history. On the other hand, the mean score of the physical neglect subscale differed according to marital status. There was a weak positive correlation between dissociative experiences and emotional abuse, physical abuse, physical neglect, and total childhood trauma questionnaire score (p <.05). It was also found that childhood trauma was a significant predictor of dissociative experiences. Conclusion: Childhood trauma was found to increase dissociative experiences in substance-dependent individuals in Eastern Turkey.